Mechanical, thermal and flame retardant properties of poly (lactic acid) / poly (methyl methacrylate) blends / Teoh, Ee Lian - Teoh, Ee Lian (2017)
Poly(lactic acid)/poly(methyl methacrylate) (PLA/PMMA) blends were prepared by melt compounding technique. Phosphorus-based flame retardant (FR) was used together with β-cyclodextrin (CD) to improve the flame resistant and thermal properties of PLA/PMMA blends. In the first stage, study was focus on the evaluation on the miscibility of PLA/PMMA blends at various blending ratio (i.e., 80/20, 60/40, 40/60, and 20/80). The evaluation was performed through thermal properties measurement [i.e., differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA)] and solvent uptake experiment. Single glass transition temperature (Tg) was detected on PLA/PMMA blends over entire composition range during DMA measurement. The solvent uptake experiment showed that PLA/PMMA20 blend exhibited smallest interaction parameter (χ12 = −0.03) according to the calculation of Flory-Huggins interaction parameter (χ12). In the second stage, phosphorus-based flame retardant (FR; 20 part per hundred resin) was added to improve the flame resistant and thermal properties of PLA/PMMA blends at blending ratio of 80/20 and 60/40.UL-94 vertical burning test and limiting oxygen index (LOI) were conducted to characterize the flame resistant properties of the blends, while thermogravimetric analyzer (TGA) was used to determine the thermal stability of the blends. Both of the PLA/PMMA20/FR and PLA/PMMA40/FR successfully achieved V-0 rating in the burning test, regardless of the PLA/PMMA blending ratio. TGA results showed that addition of FR had accelerated the thermal decomposition of PLA/PMMA20/FR and PLA/PMMA40/FR blends at low temperature, but improved the thermal stability of blends at high temperature. Higher LOI value was attained by PLA/PMMA20/FR (i.e., 31.3%) than PLA/PMMA40/FR (i.e., 28.0%), indicating PLA/PMMA20/FR having higher flame resistant properties than PLA/PMMA40/FR. In the third stage, half of the FR was replaced by CD and the efficiency of the combination in improving flame resistant and thermal properties of PLA/PMMA blend was investigated. During flammability tests, dripping behavior of the PLA/PMMA20/FR/CD was improved while maintaining its flame retardancy (i.e., UL-94 V-0; LOI = 29.3%). Higher maximum degradation temperature (Tmax) was obtained for PLA/PMMA20/FR/CD during TGA measurement, suggested the thermal degradation was delayed in the presence of CD. Scanning electron microscope (SEM) showed an extensive and compact char layer was formed on the burning surface of PLA/PMMA20/FR/CD, proving that CD could be an effective adjuvant for FR in improving flame retardancy of PLA/PMMA20/FR/CD.